Role of Nitric Oxide in Isoproterenol-Induced Myocardial Infarction - Sánchez, Victoria Chagoya de; Yañez-Maldonado, Lucía; Vidrio-Gómez, Susana; Martínez, Lidia; Suárez, Jorge; Aranda-Fraustro, Alberto; Torres, Juan Carlos; Velasco-Loyden, Gabriela (IntechOpen, 2012)
None